Substitute \(\left( 2 \right)\) for \(x\) and \(\left( 3 \right)\) for \(y\) in equation \(y' = y + xy\),
\(\begin{aligned}{}y' = y + xy\\ = \left( { \pm 2} \right) - \left( 0 \right)\left( { \pm 2} \right)\\ = \pm 2\end{aligned}\)
The values of slopes for the variables \(x\) and \(y\) for the differential equation \(y' = y + xy\) is tabulated in the below table.

Substitute \(\left( 0 \right)\) for \(y'\) in equation \(y' = y + xy\),
\(\begin{aligned}{}y' = y + xy\\\left( 0 \right) = y\left( {x + 1} \right)\end{aligned}\) and \(x = - 1\).
\(y = 0\)
The slopes are positive only when the factors \(y\) and \(x + 1\) have same sign and negative when they have opposite sign. The solution that satisfies the condition \(y\left( 0 \right) = 1\) will be a point at \(\left( {0,1} \right)\).